PEMANFAATAN MEDIA SOSIAL TIKTOK, INSTAGRAM DAN FACEBOOK DALAM MENCEGAH HATE SPEECH DI INDONESIA - Nurkarima, Alya; Tangke, Egiel Manuel; Dewi, Rizkya Mutiara (The Officium Nobile Journal, 2024)
Social media is an effective digital platform not only as a means of social interaction, but also for sharing information, communication and exchange of information. In Indonesia, social networks or social media such as TikTok, Instagram and Facebook have become an important part of our daily lives. It cannot be denied that Indonesia is one of the countries that talks the most with social media users in the world. Unfortunately, the literacy level of Indonesian society is low, resulting in a loss of control and poor teaching. Therefore, research regarding the use of these platforms to prevent hate speech in Indonesia is an important issue. In Indonesia, social media users play an important role in spreading good news and actively preventing bad news. The research method used is an exploratory descriptive approach which allows a thorough analysis of the strategies, policies and trends implemented by TikTok, Instagram and Facebook. According to the study, TikTok, Instagram, and Facebook have adopted various prevention strategies, including news reporting systems, information analysis, and public awareness programs. However, challenges remain, not only in terms of effectiveness in finding and processing negative information, but also in encouraging positive attitudes and engagement among users. This study provides suggestions to policy makers, social media practitioners, and users to increase the role of social media as a tool to prevent negative communication and encourage excellence in education and digital literacy in Indonesian society.